SOSIALISASI TEKNIK DASAR BOLA BASKET PADA SISWA EKTRAKURIKULER BOLA BASKET SD AL AZHAR 37 PEKANBARU - Oki Candra; Zulrafli Zulrafli; Kamarudin Kamarudin; Ahmad Rahmadani (JURNAL PENGABDIAN MANDIRI, 2023)
The purpose of this community service is to socialize basic basketball techniques to extracurricular basketball students at SD AL Azhar 37 Pekanbaru. The method used in this service is lectures and presentations followed by practice with kelpangan. This service was carried out on February 22, 2023 in the field of SD Al Azhar 27 Pekanbaru. The results of this service have a positive impact on this service, which so far has only made random movements, but with this dedication it can be seen directly in the field, extracurricular students carry out technical movements and technical steps for dribbling, passing and shooting. With the hope that after this extracurricular activity, students will continue to learn how to make the right moves according to the basic technique.